Factors concerned in the efficient steam sterilization of surgical dressings. Issue 5 (September 1961) - Fallon, R. J.
Abstract : Some of the factors affecting the efficient steam sterilization of dressings have been examined. A jacketed sterilizer will process a load more quickly than a sterilizer without a jacket. The level of fore-vacuum is critical and must reach an absolute pressure of 20 mm. Hg (29·2 in.Hg vacuum) or less. This will overcome all conditions of overpacking studied. The level of after-vacuum should be 100 mm. Hg absolute or less, preferably near 50 mm. Hg absolute. Overpacking cannot be defined in terms of weight of a fabric per unit volume of container but occurs when a load is compressed in its container.